The implementation of the List of Job Posts (RPT) on a Galician local administration - Seoane, Francisco Jesús Ferreiro (2017)
The objective of this paper is the analysis of the List of Job Posts (RPT in Spanish), an instrument used by public administrations and quite demanded by local entities whose aim is to define the tasks and conditions of each work post and to order the organizational structure of the personnel within the public sector. Every elaboration of a RPT starts with a description of the job posts, which means to make a detailed exposition of the characteristics inherent in them. To do that, we will use the technic of report and interview as instrument of collection and verification of data; followed by the technical and economic valuation of the job posts to establish the specific complement perceived by each one’s performance.The main result is the great utility of the RPT,which allows to improve the organizational efficacy of the Public Administrationand solve conflicts among the staff. The main limitations appear in the difficulty of having a consensus about a RPT as the expectations of the interested are not always satisfied making the process of negotiation more complex, getting to the point of no approval. The main contributions of this article are the review of the theoretical framework of the RPT, not studied deeply in the academic field, and the exposition of a methodology that allows to modernize its implementation, valuing the job posts technical and economically through objective factors reducing arbitrariness and repairing historical anomalies based on subjective criteria.